A Review of Web-Based Immunization Information System of Ernakulam District “Unite for Healthy Ernakulam, Kerala (U4HE)”: Perceived End-User Barriers - Shakeer, Irfan; Narayanan, Prakash; Baby, Anju (National Journal of Community Medicine, 2023)
Background: Reported coverage estimates for vaccine have the inherent problem of missing private entity data, to circumvent this, the National Health Mission, Ernakulam, designed and implemented an Immunization Information System (IIS) to collect routine vaccination reports from the private sector. This study attempted to identify the barriers to reporting by the private sector. Methodology: The study was conducted in Kerala's Ernakulam district. The design of the study was cross-sectional. The end–users, who are from the private sector, were the participants of 28 in-depth interviews in the study. Results: The new reporting system has increased private sector involvement in information exchange, all 78 private hospitals (100%) were reporting to NHM Ernakulam. But the completeness of reporting was not uniform. Major barriers identified were the lack of IIS interoperability with the hospital information system (HIS) being used by the private hospitals, variance because of lack of training of staff entering the data, and the unavailability of dedicated staff for reporting data. Conclusion: Addressing these barriers could improve the reporting of routine vaccination data from the private sector.